Spatial patterns in the formation of economic preferences - Shyamal K. Chowdhury; Manuela Puente-Beccar; Hannah Schildberg-Hörisch; Sebastian O. Schneider; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2025)
We investigate how strongly the local environment beyond the family can contribute to understanding the formation of children's economic preferences. Building on precise geolocation data for around 6000 children, we use fixed effects, spatial autoregressive models and Kriging to capture the relation between the local environment and children's preferences. The spatial models explain a considerable part of so far unexplained variation in preferences. Moreover, the "spatial stability" of preferences exceeds the village level. Our results highlight the importance of the local environment for the formation of children's preferences, which we quantify to be as large as that of parental preferences.
hdl:21.11116/0000-0011-7B26-9
Keywords: D01; C21; C99; 330; skill formation; spatial models; kriging; local environment; patience; risk attitudes; prosociality; experiments with children; Bangladesh